SKRINING FITOKIMIA DAN UJI ANTIBAKTERI Streptococcus mutans DARI EKSTRAK DAUN KANGKUNG PAGAR (Ipomoea carnea Jacq) - Alifah Rahmania Fadhilah; Dedeh Komalasari; Ermi Abriyani; Iin Lidia Putama Mursal (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2022)
Dental caries is one of the most common dental health problems and is the main problem of dental and oral disease. the most common cause of dental caries is Streptococcus mutans bacteria. To treat dental caries, one of the plants that can be used is the leaf of kale fence (Ipomoea carnea Jacq, which has antibacterial properties. This study aims to determine the compound content of n-hexane, methanol, ethyl acetate and the antibacterial activity of Streptococcus mutans. This research used well diffusion method and tested against Streptococcus mutans bacteria. Thus, it was found that the compound content of the thick extract of kale leaves contains compounds of steroidal n-hexane, methanol flavonoids, saponins, tannins, triterpenoids, and ethyl acetate alkaloids, flavonoids, steroids, tannins and simplicia dried kale leaves contain alkaloids, flavonoids. , steroids, tannins. The results of the activity test of the leaf extract of kale (Ipomoea carnea Jacq) inhibited the growth of Streptococcus mutans bacteria with a concentration of 100% n-hexane inhibition zone 5.2 mm in the weak category, methanol 16.4 mm in the very strong category and ethyl acetate 10.4 mm in the strong category. . Based on the results, it was shown that the leaf of kale (Ipomoea carnea Jacq) had antibacterial activity from Streptococcus mutans bacteria.